A composite peeling layer for ultra-thin copper foil of carrier and its application

By forming a shell polychen spales on the carrier copper foil and the organic coating of polyiline and sedimentation of nanof chromium metal layers, the problem of poor conductivity and uneven peeling of composite peeling layer, and realized the complete and safe preparation of ultra -thin copper foil. process.

CN117626365BActive Publication Date: 2025-01-24GUANGDONG YINGHUA ELECTRONIC TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311684668.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-08
Publication Date
2025-01-24
Estimated Expiration
2043-12-08

AI Technical Summary

Technical Problem

In the preparation process of ultra-thin copper foil, the existing composite peeling layer has problems such as poor conductivity, uneven peeling or difficulty in peeling, and incomplete ultra-thin copper foil.

Method used

Chitosan-grafted polyaniline is used as the organic coating, and a nano-chromium metal layer is deposited on the carrier copper foil through electrochemical method to form a composite peeling layer. This method not only improves the conductivity of the organic layer and the adsorption capacity of Cr3+, but also reduces the binding force between the carrier and the ultra-thin copper foil, improving the peeling performance.

Benefits of technology

It achieves the improvement of the conductivity of the composite peeling layer, the optimization of the peeling performance and the integrity guarantee of the ultra-thin copper foil, and uses trivalent chromium sulfate as the electroplating solution, which is safe and pollution-free.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117626365B_ABST
    Figure CN117626365B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of ultra-thin copper foil preparation, and relates to a composite peeling layer for a carrier ultra-thin copper foil and its application. The composite peeling layer includes an organic coating and a metal plating layer; the organic coating is prepared from chitosan and polyaniline; the metal plating layer is a metal chromium plating layer. After chitosan is grafted with polyaniline, the adsorption performance of metal ions is greatly improved, and the conductivity of the organic coating is improved by means of the conductive property of polyaniline itself. Chitosan and aniline are loaded on the carrier copper foil by an electrochemical method, and then a chromium metal layer is deposited to obtain a composite peeling layer. The composite peeling layer has strong chromium adsorption capacity, excellent conductivity, uniform thickness, and is easy to peel off, and is widely used in the preparation of ultra-thin copper foil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ultra-thin copper foil preparation, and relates to a composite peeling layer for a carrier ultra-thin copper foil and application thereof. Background Art

[0002] The copper foil used for PCB circuit boards is developing in a lighter and thinner direction. However, the thinner the copper foil, the easier it is to wrinkle and tear during production and transportation. Ultra-thin copper foil can be prepared by attaching a carrier. For example, Japan Mitsui Metals & Chemicals Co., Ltd. disclosed in its invention patent CN1159958C that ultra-thin copper foil is prepared by electroplating using copper or copper alloy as a carrier. The carrier layer currently used is usually an electrolytic copper foil of 18-35 microns, and a peeling layer is formed on the carrier, and then an ultra-thin copper foil of 2-6 microns is deposited. When in use, the ultra-thin copper foil needs to be pressed with the resin, and then the carrier copper foil layer is peeled off; in this preparation process, the peeling layer is the key to preparing ultra-thin copper foil.

[0003] In the preparation process of ultra-thin copper foil, the peeling layer is mainly divided into an inorganic peeling layer, an organic peeling layer and a composite peeling layer. The inorganic peeling layer is mainly a metal or alloy layer with good conductivity, but it is difficult to peel off. Chinese invention patent CN108330517B discloses a plating solution for a carrier copper foil peeling layer and a method for preparing the peeling layer. The plating solution is prepared with potassium hydrogen tartrate, zinc sulfate and additives, and the carrier copper is immersed in it. Then, a nano-scale composite zinc-plated peeling layer can be electroplated on the carrier copper foil. The peeling layer is extremely thin and uniform; however, it has a strong bonding force with the copper foil, the peeling layer effect is not good after hot pressing, and the zinc-plated layer is easy to damage the ultra-thin copper foil.

[0004] The composite peeling layer usually uses an organic layer and an inorganic layer together as the peeling layer, which is the focus of current research. The organic peeling layer is mainly nitrogen-containing compounds, sulfur-containing compounds and carboxylic acids, and benzotriazole and carboxylbenzotriazole are commonly used. Chinese invention patent application CN112853408A discloses a method for preparing an ultra-thin copper foil with a carrier that is easy to peel and has a pure interface. The peeling layer is a composite peeling layer composed of an alloy layer and an organic layer. The organic layer is obtained by coating an organic liquid; and the alloy layer is achieved by electroplating an alloy liquid containing a complexing agent and at least one of soluble sulfates (nickel sulfate, zinc sulfate, cobalt sulfate, titanium sulfate and iron sulfate). The composite peeling layer has stable peeling performance and easy peeling characteristics after high-temperature pressing; however, the organic peeling layer has poor conductivity, and uneven adsorption of organic matter leads to uneven peeling.

[0005] Chinese invention patent application CN107475698A discloses a method for preparing a Ni-Cr-BP ultra-thin copper foil peeling layer. The peeling layer is prepared by adding a solution of nickel sulfate and chromium chloride to a solution of sodium hypophosphite, sodium fluoride, sodium benzothiazole, and citric acid, and then adjusting the pH value with alkali solution, and then preparing it by potassium borohydride chemical plating. The peeling layer has the characteristics of good thermal stability, stable peeling strength, and low industrial cost. However, the ultra-thin copper foil is easy to fall off partially or completely from the carrier copper foil during use, resulting in incomplete ultra-thin copper foil.

[0006] Chinese invention patent application CN115948773A discloses a composite stripping layer using crystalline nickel and an amorphous chromium plating layer. The van der Waals force between the amorphous chromium plating layer and the ultra-thin copper foil is weak, easy to strip, and has fine grains and a pure interface. Chinese invention patent application CN113388868A discloses a method for self-stripping of copper foil by electro-depositing a layer of discrete Cr crystal nuclei on the surface of the copper foil. The use of trivalent chromium avoids the toxicity of hexavalent chromium, making it more environmentally friendly. It only takes a few seconds to deposit the Cr crystal nuclei, the deposited stripping layer is evenly distributed, and the method is simple and easy to operate. However, the stability of the trivalent chromium solution is poor.

[0007] In summary, although there are many studies on composite peeling layers, there is no peeling layer that can be completely and stably peeled. It is urgent to develop a peeling layer that is simple to operate, has good coating conductivity, is easy to peel, and has little environmental pollution. Summary of the invention

[0008] The present invention aims to solve the problems of poor conductivity of the composite peeling layer, uneven or difficult peeling, and incomplete ultra-thin copper foil after peeling in the prior art, and provides a composite peeling layer for a carrier ultra-thin copper foil and its application. After chitosan is grafted with polyaniline, the adsorption performance of metal ions is greatly improved. At the same time, polyaniline itself has conductivity, which greatly improves the conductivity of the organic coating. Chitosan and aniline are electrochemically deposited on the carrier copper foil, and then a nano-chromium metal layer is deposited on the composite film to obtain a composite peeling layer.

[0009] The technical solution of the present invention is as follows:

[0010] The invention provides a composite peeling layer for a carrier ultra-thin copper foil, the composite peeling layer comprising an organic coating and a metal plating layer; the organic coating is prepared from chitosan and polyaniline; the metal plating layer is a metal chromium plating layer.

[0011] Furthermore, the preparation method of the organic coating is as follows:

[0012] S11: dissolving chitosan in an organic acid solution, adding ethanol, heating and stirring to dissolve, adding a cross-linking agent, and stirring to obtain a chitosan pretreatment solution;

[0013] S12: dissolving aniline in phosphoric acid solution to obtain aniline solution;

[0014] S13: adding the chitosan pretreatment solution to the aniline solution to obtain an electrodeposition solution;

[0015] S14: Immersing the carrier copper foil in an electroplating solution to obtain the copper foil by electroplating.

[0016] Furthermore, the chitosan has a deacetylation degree of 80-95% and a concentration of 5-20% (w / v) in the electrodeposition solution.

[0017] Furthermore, the cross-linking agent is any one of glutaraldehyde, dopamine, ethylene glycol diacid and glucuronic acid, and the concentration is 1-6wt%.

[0018] Furthermore, the mass ratio of chitosan to cross-linking agent is 40-100:1.

[0019] Furthermore, the concentration of aniline is 0.2-0.5 mol / L; the concentration of acetic acid is 1-5 wt%; and the concentration of phosphoric acid is 0.2-0.5 mol / L.

[0020] Furthermore, the electrodeposition is a constant current method with a current density of 0.03-0.08 mA / cm 2 , the electrodeposition time is 6min-3h.

[0021] In some embodiments of the present invention, the carrier copper foil needs to be pretreated before electrodeposition, and the specific steps are as follows:

[0022] (1) Preparation of alkaline treatment solution:

[0023] (2) immersing the carrier copper foil in an alkaline treatment solution;

[0024] (3) Wash with ethanol and water in sequence.

[0025] In the present invention, the pretreatment of the carrier copper foil can not only remove the grease and impurities on the surface of the base film, but also introduce groups such as carboxyl groups on the surface to improve the adhesion of the base film.

[0026] Furthermore, the preparation method of the metal chromium plating layer is as follows:

[0027] S21: adding chromium sulfate, boric acid, ammonium acetate and sodium dodecyl sulfate into water, stirring and dissolving to obtain a metal plating solution;

[0028] S22: Immersing the carrier copper foil with the electrodeposited organic coating into a metal electroplating solution and subjecting it to electroplating treatment to obtain the product.

[0029] Furthermore, the mass ratio of the chromium sulfate, boric acid, ammonium acetate and sodium dodecyl sulfate is 20-100:60-80:10-40:0.01-0.1.

[0030] Furthermore, the electroplating temperature is 20-50°C; the current density is 0.5-1 mA / cm 2 , the plating time is 5-30s.

[0031] Furthermore, the thickness of the organic coating is 100nm-1μm.

[0032] Furthermore, the thickness of the metal coating is 50-200 nm.

[0033] The present invention also provides the use of any of the above-mentioned composite peeling layers in the preparation of ultra-thin copper foil.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] (1) Chitosan has hydroxyl, amino and N-acetyl groups that can react with metal ions Cr. 3+ Coordination and chelation can obtain a denser chromium coating, which can significantly reduce the bonding force between the carrier and the ultra-thin copper foil, and the peeling performance is better;

[0036] (2) The in-situ polymerization method forms a polyaniline layer on the surface of the carrier copper foil, which is easy to operate. After chitosan is grafted with polyaniline, it can not only improve the organic layer's 3+ The adsorption capacity can also improve the conductivity of the organic layer; in addition, the electrochemical film formation is not only fast, but also can improve the conductivity of the organic stripping layer, which is more conducive to the subsequent electroplating of copper foil;

[0037] (3) Trivalent chromium sulfate is used as the main component of the electroplating solution, which is safe and pollution-free. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a schematic diagram of the structure of the carrier ultra-thin copper foil;

[0039] Figure numerals: 1. Carrier copper foil layer; 2. Organic coating layer; 3. Metal plating layer; 4. Ultra-thin copper foil layer. DETAILED DESCRIPTION

[0040] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, which should also fall within the scope of the present invention.

[0041] Example 1

[0042] A carrier ultra-thin copper foil (structure such as Figure 1 As shown), it includes a carrier copper foil layer 1, an organic coating 2, a metal plating layer 3 and an ultra-thin copper foil layer 4.

[0043] The preparation process is as follows:

[0044] 1. Pretreatment of carrier copper foil:

[0045] Preparation of KOH and NaHCO 3 in ethanol aqueous solution (where KOH concentration is 2M, NaHCO 3 The concentration is 0.5M, and the volume ratio of ethanol to water is 2:1), the carrier copper foil is immersed in the above solution and treated for 5 minutes; the carrier copper foil is taken out and washed with ethanol and water in turn.

[0046] 2. Preparation of organic coating:

[0047] (1) Take 20g of chitosan (95% deacetylation degree) and dissolve it in 90mL of 5wt% acetic acid solution, add 10mL of anhydrous ethanol, heat to 50°C, and stir for 1h to completely acid-hydrolyze the chitosan; add 4g of 5wt% glutaraldehyde crosslinking agent (chitosan / glutaraldehyde mass ratio is 100:1) and continue stirring for 2h to obtain a chitosan pretreatment solution;

[0048] (2) Mix 50 mL of aniline (0.3 M) and 50 mL of phosphoric acid (0.3 M) to obtain a mixed solution;

[0049] (3) adding the chitosan pretreatment solution of step (1) to the mixed solution of step (2) to obtain an electrodeposition solution (wherein the chitosan concentration is 10% (w / v));

[0050] (4) Using constant current deposition method, set the current density to 0.05 mA / cm 2 , the electrodeposition time is 30 min, and a carrier copper foil loaded with an organic coating is obtained;

[0051] (5) The organic-coated carrier copper foil was cleaned with anhydrous ethanol and deionized water, respectively, and dried at 100°C.

[0052] 3. Preparation of metal coating:

[0053] (1) adding chromium sulfate, boric acid, ammonium acetate, and sodium dodecyl sulfate in a mass ratio of 50:70:30:0.05 to 100 mL of water, stirring and dissolving to obtain a metal plating solution;

[0054] (2) Raise the temperature of the metal plating solution to 50°C and immerse the material dried in step 2 into the metal plating solution; set the current density to 0.5 mA / cm 2 , the electroplating time is 30s, and you get it.

[0055] 4. Preparation of ultra-thin copper foil layer:

[0056] (1) 7.83 g of copper sulfate pentahydrate, 0.0005 mg of collagen, 0.0005 mg of hydroxyethyl cellulose, and 0.0015 mg of sodium chloride were added to 100 mL of water to obtain a copper plating solution;

[0057] (2) Raise the plating solution temperature to 50°C, immerse the cleaned material obtained in step 3 in the copper plating solution, and set the current density to 400 mA / cm 2 , the electroplating time is 20s, and you get it.

[0058] 5. Anti-oxidation treatment:

[0059] The material obtained in step 4 was immersed in an anti-oxidation liquid (a mixture of 1 g / L benzotriazole and 1 g / L benzoic acid) for 5 seconds, and the liquid was squeezed out by a water-collecting roller, dried by hot air at 100°C, and rolled up.

[0060] 6. Lamination treatment:

[0061] The anti-oxidation treated composite copper foil was pressed onto the PCB board at 180°C for 1 hour and cured, and then the carrier copper foil was peeled off by mechanical means to obtain an ultra-thin copper foil.

[0062] Example 2

[0063] A carrier ultra-thin copper foil, the structure of which is the same as that of embodiment 1;

[0064] Preparation process:

[0065] The preparation process is as follows:

[0066] 1. Pretreatment of carrier copper foil:

[0067] Preparation of KOH and NaHCO 3 in ethanol aqueous solution (where KOH concentration is 1 M, NaHCO 3 The concentration is 1M, and the volume ratio of ethanol to water is 1:1), the carrier copper foil is immersed in the above solution and treated for 5 minutes; the carrier copper foil is taken out and washed with ethanol and water in turn.

[0068] 2. Preparation of organic coating:

[0069] (1) 10 g of chitosan (95% deacetylation degree) was dissolved in 90 mL of 1 wt% acetic acid solution, 10 mL of anhydrous ethanol was added, the mixture was heated to 50°C, and the mixture was stirred for 1 h to completely hydrolyze the chitosan; 4 g of 5 wt% glutaraldehyde crosslinking agent (mass ratio of chitosan to glutaraldehyde was 50:1) was added and the mixture was stirred for 2 h to obtain a chitosan pretreatment solution;

[0070] (2) Mix 50 mL of aniline (0.2 M) and 50 mL of phosphoric acid (0.2 M) to obtain a mixed solution;

[0071] (3) adding the chitosan pretreatment solution of step (1) to the mixed solution of step (2) to obtain an electrodeposition solution (wherein the chitosan concentration is 5% (w / v));

[0072] (4) Using constant current deposition method, set the current density to 0.05 mA / cm 2 , the electrodeposition time is 30 min, and a carrier copper foil loaded with an organic coating is obtained;

[0073] (5) The organic-coated carrier copper foil was cleaned with anhydrous ethanol and deionized water, respectively, and dried at 100°C.

[0074] 3. Preparation of metal coating:

[0075] (1) adding chromium sulfate, boric acid, ammonium acetate, and sodium dodecyl sulfate in a mass ratio of 100:60:10:0.01 to 100 mL of water, stirring and dissolving to obtain a metal plating solution;

[0076] (2) Raise the temperature of the metal plating solution to 50°C and immerse the material dried in step 2 into the metal plating solution; set the current density to 0.5 mA / cm 2 , the electroplating time is 30s, and you get it.

[0077] 4. Preparation of ultra-thin copper foil layer:

[0078] (1) 7.83 g of copper sulfate pentahydrate, 0.0005 mg of collagen, 0.0005 mg of hydroxyethyl cellulose, and 0.0015 mg of sodium chloride were added to 100 mL of water to obtain a copper plating solution;

[0079] (2) Raise the plating solution temperature to 50°C, immerse the cleaned material obtained in step 3 in the copper plating solution, and set the current density to 400 mA / cm 2 , the electroplating time is 20s, and you get it.

[0080] 5. Anti-oxidation treatment:

[0081] The material obtained in step 4 was immersed in an anti-oxidation liquid (a mixture of 1 g / L benzotriazole and 1 g / L benzoic acid) for 5 seconds, and the liquid was squeezed out by a water-collecting roller, dried by hot air at 100°C, and rolled up.

[0082] 6. Lamination treatment:

[0083] The anti-oxidation treated composite copper foil was pressed onto the PCB board at 180°C for 1 hour and cured, and then the carrier copper foil was peeled off by mechanical means to obtain an ultra-thin copper foil.

[0084] Example 3

[0085] A carrier ultra-thin copper foil, the structure of which is the same as that of embodiment 1;

[0086] Preparation process:

[0087] The preparation process is as follows:

[0088] 1. Pretreatment of carrier copper foil:

[0089] Preparation of KOH and KHCO 3 in an ethanol aqueous solution (where KOH concentration is 0.5 M, KHCO 3 The concentration is 2M, and the volume ratio of ethanol to water is 2:1), the carrier copper foil is immersed in the above solution and treated for 5 minutes; the carrier copper foil is taken out and washed with ethanol and water in turn.

[0090] 2. Preparation of organic coating:

[0091] (1) 10 g of chitosan (90% deacetylation degree) was dissolved in 90 mL of 3 wt% acetic acid solution, 10 mL of anhydrous ethanol was added, the mixture was heated to 50°C, and the mixture was stirred for 1 h to completely hydrolyze the chitosan; 8.33 g of 2.0 wt% glutaraldehyde crosslinking agent (mass ratio of chitosan to glutaraldehyde was 60:1) was added and the mixture was stirred for 2 h to obtain a chitosan pretreatment solution;

[0092] (2) Mix 50 mL of aniline (0.5 M) and 50 mL of phosphoric acid (0.5 M) to obtain a mixed solution;

[0093] (3) adding the chitosan pretreatment solution of step (1) to the mixed solution of step (2) to obtain an electrodeposition solution (wherein the chitosan concentration is 5% (w / v));

[0094] (4) Using constant current deposition method, set the current density to 0.05 mA / cm 2 , the electrodeposition time is 30 min, and a carrier copper foil loaded with an organic coating is obtained;

[0095] (5) The organic-coated carrier copper foil was cleaned with anhydrous ethanol and deionized water, respectively, and dried at 100°C.

[0096] 3. Preparation of metal coating:

[0097] (1) adding chromium sulfate, boric acid, ammonium acetate, and sodium dodecyl sulfate in a mass ratio of 20:80:40:0.1 to 100 mL of water, stirring and dissolving to obtain a metal plating solution;

[0098] (2) Raise the temperature of the metal plating solution to 50°C and immerse the material dried in step 2 into the metal plating solution; set the current density to 0.5 mA / cm 2 , the electroplating time is 30s, and you get it.

[0099] 4. Preparation of ultra-thin copper foil layer:

[0100] (1) 8.73 g of copper sulfate pentahydrate, 0.0005 mg of collagen, 0.0005 mg of hydroxyethyl cellulose, and 0.0015 mg of sodium chloride were added to 100 mL of water to obtain a copper plating solution;

[0101] (2) Raise the plating solution temperature to 50°C, immerse the cleaned material obtained in step 3 in the copper plating solution, and set the current density to 400 mA / cm 2 , the electroplating time is 20s, and you get it.

[0102] 5. Anti-oxidation treatment:

[0103] The material obtained in step 4 was immersed in an anti-oxidation liquid (a mixture of 1 g / L benzotriazole and 1 g / L benzoic acid) for 5 seconds, and the liquid was squeezed out by a water-collecting roller, dried by hot air at 100°C, and rolled up.

[0104] 6. Lamination treatment:

[0105] The anti-oxidation treated composite copper foil was pressed onto the PCB board at 180°C for 1 hour and cured, and then the carrier copper foil was peeled off by mechanical means to obtain an ultra-thin copper foil.

[0106] Example 4

[0107] A carrier ultra-thin copper foil, the structure of which is the same as that of embodiment 1;

[0108] Preparation process:

[0109] The preparation process is as follows:

[0110] 1. Pretreatment of carrier copper foil:

[0111] Preparation of NaOH and NaHCO 3 in ethanol aqueous solution (where NaOH concentration is 2M, NaHCO 3 The concentration is 0.5M, and the volume ratio of ethanol to water is 2:1), the carrier copper foil is immersed in the above solution and treated for 5 minutes; the carrier copper foil is taken out and washed with ethanol and water in turn.

[0112] 2. Preparation of organic coating:

[0113] (1) 40 g of chitosan (deacetylation degree 85%) was dissolved in 90 mL of 5 wt % acetic acid solution, 10 mL of anhydrous ethanol was added, the mixture was heated to 50° C., and stirred for 1 h to completely hydrolyze the chitosan; 12.5 g of 4.0% glutaraldehyde crosslinking agent (mass ratio of chitosan to glutaraldehyde was 80:1) was added, and stirring was continued for 2 h to obtain a chitosan pretreatment solution;

[0114] (2) Mix 50 mL of aniline (0.2 M) and 50 mL of phosphoric acid (0.5 M) to obtain a mixed solution;

[0115] (3) adding the chitosan pretreatment solution of step (1) to the mixed solution of step (2) to obtain an electrodeposition solution (wherein the chitosan concentration is 20% (w / v));

[0116] (4) Using constant current deposition method, set the current density to 0.05 mA / cm 2 , the electrodeposition time is 30 min, and a carrier copper foil loaded with an organic coating is obtained;

[0117] (5) The organic-coated carrier copper foil was cleaned with anhydrous ethanol and deionized water, respectively, and dried at 100°C.

[0118] 3. Preparation of metal coating:

[0119] (1) adding chromium sulfate, boric acid, ammonium acetate, and sodium dodecyl sulfate in a mass ratio of 50:70:40:0.01 to 100 mL of water, stirring and dissolving to obtain a metal plating solution;

[0120] (2) Raise the temperature of the metal plating solution to 50°C and immerse the material dried in step 2 into the metal plating solution; set the current density to 0.5 mA / cm 2 , the electroplating time is 30s, and you get it.

[0121] 4. Preparation of ultra-thin copper foil layer:

[0122] (1) 8.73 g of copper sulfate pentahydrate, 0.0005 mg of collagen, 0.0005 mg of hydroxyethyl cellulose, and 0.0015 mg of sodium chloride were added to 100 mL of water to obtain a copper plating solution;

[0123] (2) Raise the plating solution temperature to 50°C, immerse the cleaned material obtained in step 3 in the copper plating solution, and set the current density to 400 mA / cm 2 , the electroplating time is 20s, and you get it.

[0124] 5. Anti-oxidation treatment:

[0125] The material obtained in step 4 was immersed in an anti-oxidation liquid (a mixture of 1 g / L benzotriazole and 1 g / L benzoic acid) for 5 seconds, and the liquid was squeezed out by a water-collecting roller, dried by hot air at 100°C, and rolled up.

[0126] 6. Lamination treatment:

[0127] The anti-oxidation treated composite copper foil was pressed onto the PCB board at 180°C for 1 hour and cured, and then the carrier copper foil was peeled off by mechanical means to obtain an ultra-thin copper foil.

[0128] Example 5

[0129] A carrier ultra-thin copper foil, the structure of which is the same as that of embodiment 1;

[0130] Preparation process:

[0131] The preparation process is as follows:

[0132] 1. Pretreatment of carrier copper foil:

[0133] Preparation of KOH and KHCO 3 in ethanol aqueous solution (where KOH concentration is 2M, NaHCO 3 The concentration is 0.5M, and the volume ratio of ethanol to water is 1:1), the carrier copper foil is immersed in the above solution and treated for 5 minutes; the carrier copper foil is taken out and washed with ethanol and water in turn.

[0134] 2. Preparation of organic coating:

[0135] (1) 40 g of chitosan (80% deacetylation degree) was dissolved in 90 mL of 5 wt% acetic acid solution, 10 mL of anhydrous ethanol was added, and the mixture was heated to 50°C and stirred for 1 h to completely acid-lyze the chitosan; 13.33 g of 6.0% dopamine cross-linking agent (mass ratio of chitosan to dopamine was 50:1) was added and stirred for 2 h to obtain a chitosan pretreatment solution;

[0136] (2) Mix 50 mL of aniline (0.5 M) and 50 mL of phosphoric acid (0.2 M) to obtain a mixed solution;

[0137] (3) adding the chitosan pretreatment solution of step (1) to the mixed solution of step (2) to obtain an electrodeposition solution (wherein the chitosan concentration is 20% (w / v));

[0138] (4) Using constant current deposition method, set the current density to 0.05 mA / cm 2 , the electrodeposition time is 30 min, and a carrier copper foil loaded with an organic coating is obtained;

[0139] (5) The organic-coated carrier copper foil was cleaned with anhydrous ethanol and deionized water, respectively, and dried at 100°C.

[0140] 3. Preparation of metal coating:

[0141] (1) adding chromium sulfate, boric acid, ammonium acetate, and sodium dodecyl sulfate in a mass ratio of 50:70:10:0.1 to 100 mL of water, stirring and dissolving to obtain a metal plating solution;

[0142] (2) Raise the temperature of the metal plating solution to 50°C and immerse the material dried in step 2 into the metal plating solution; set the current density to 0.5 mA / cm 2 , the electroplating time is 30s, and you get it.

[0143] 4. Preparation of ultra-thin copper foil layer:

[0144] (1) 8.73 g of copper sulfate pentahydrate, 0.0005 mg of collagen, 0.0005 mg of hydroxyethyl cellulose, and 0.0015 mg of sodium chloride were added to 100 mL of water to obtain a copper plating solution;

[0145] (2) Raise the plating solution temperature to 50°C, immerse the cleaned material obtained in step 3 in the copper plating solution, and set the current density to 400 mA / cm 2 , the electroplating time is 20s, and you get it.

[0146] 5. Anti-oxidation treatment:

[0147] The material obtained in step 4 was immersed in an anti-oxidation liquid (a mixture of 1 g / L benzotriazole and 1 g / L benzoic acid) for 5 seconds, and the liquid was squeezed out by a water-collecting roller, dried by hot air at 100°C, and rolled up.

[0148] 6. Lamination treatment:

[0149] The anti-oxidation treated composite copper foil was pressed onto the PCB board at 180°C for 1 hour and cured, and then the carrier copper foil was peeled off by mechanical means to obtain an ultra-thin copper foil.

[0150] Comparative Example 1

[0151] The only difference from Example 1 is that chitosan is replaced by an equal amount of chitin.

[0152] Comparative Example 2

[0153] The only difference from Example 1 is that the deacetylation degree of chitosan is 50%.

[0154] Comparative Example 3

[0155] The only difference from Example 1 is that chitosan is replaced by glucosamine.

[0156] Comparative Example 4

[0157] The only difference from Example 1 is that in step (1), the amount of chitosan used is 5 g.

[0158] Comparative Example 5

[0159] The only difference from Example 1 is that in step (1), the amount of chitosan used is 50 g.

[0160] Comparative Example 6

[0161] The only difference from Example 1 is that chitosan is not added to the organic coating, and only aniline solution is electrodeposited to obtain a polyaniline layer.

[0162] Comparative Example 7

[0163] The only difference from Example 1 is that the release layer is only an organic coating and no metal coating is prepared.

[0164] Comparative Example 8

[0165] The only difference from Example 1 is that the release layer is only a metal coating, and no organic coating is prepared.

[0166] The relevant performance characterization results of the ultra-wave copper foil prepared in the comparative example of the embodiment of the present invention are shown in Table 1.

[0167] Table 1 Composite copper foil performance characterization results

[0168]

[0169]

[0170] Comparative Examples 1-2 can be seen from Example 1 that when the deacetylation degree of chitin or chitosan is insufficient, peeling is difficult, which may be related to its solubility. The solubility decreases, resulting in poor film-forming properties, affecting the uniformity of subsequent copper plating, and the copper foil is thin in some areas, resulting in uneven peeling; Comparative Example 6 is compared with Example 1, and chitosan is not used. The adsorption capacity of polyaniline to Cr in the organic coating is insufficient, and the organic layer partially adheres to the copper layer, resulting in incomplete peeling and inability to peel; and Comparative Example 3 uses an equal amount of substances with amino and hydroxyl groups to replace the chitosan of the present invention, and its peeling strength also decreases to a certain extent, and the cost is high, which is not suitable for industrial production. Using the Cr metal layer alone can also achieve complete peeling, but adding chitosan and polyaniline layers will make the Cr layer more dense and uniform. This is an organic-inorganic composite peeling layer, and the effect is theoretically better than that of a simple metal Cr layer.

[0171] Compared with Example 1, the amount of chitosan used in Comparative Examples 4 and 5 also has a certain influence on the stripping performance of the ultra-thin copper foil. When the amount of chitosan used is too low, the thickness of the organic coating formed is small, and the adsorption capacity of Cr is insufficient; when the amount of chitosan used is too high, the thickness of the organic coating formed is too large, the copper plating is uneven, etc., which is also not conducive to the stripping of the ultra-thin copper foil.

[0172] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A composite peeling layer for a carrier ultra-thin copper foil, characterized in that: The composite peeling layer includes an organic coating and a metal plating layer; the organic coating is prepared from chitosan and polyaniline; the metal plating layer is a metal chromium plating layer; The deacetylation degree of the chitosan is 80-95%; The preparation method of the organic coating is as follows: S11: dissolving chitosan in an organic acid solution, adding ethanol, heating and stirring to dissolve, adding a cross-linking agent, and stirring to obtain a chitosan pretreatment solution; S12: dissolving aniline in phosphoric acid solution to obtain aniline solution; S13: adding the chitosan pretreatment solution to the aniline solution to obtain an electrodeposition solution; S14: immersing the carrier copper foil into an electrodeposition solution to obtain the copper foil by electrodeposition; The mass ratio of chitosan to cross-linking agent is 40-100:

1.

2. The composite peeling layer according to claim 1, characterized in that: The chitosan has a concentration of 5-20% (w / v) in the electrodeposition solution; the cross-linking agent is any one of glutaraldehyde, dopamine, ethylene glycol diacid and glucuronic acid, and the concentration is 1-6wt%.

3. The composite peeling layer according to claim 1, characterized in that: The concentration of the aniline is 0.2-0.5 mol / L; the concentration of the organic acid solution is 1-5 wt%; and the concentration of the phosphoric acid is 0.2-0.5 mol / L.

4. The composite peeling layer according to claim 1, characterized in that: In step S14, the electrodeposition is performed by constant current method with a current density of 0.03-0.08 mA / cm 2 , the electrodeposition time is 6min-3h.

5. The composite peeling layer according to claim 1, characterized in that: The preparation method of the metal chromium plating layer is as follows: S21: adding chromium sulfate, boric acid, ammonium acetate and sodium dodecyl sulfate into water, stirring and dissolving to obtain a metal plating solution; S22: Immersing the carrier copper foil with the electrodeposited organic coating into a metal electroplating solution and subjecting it to electroplating treatment to obtain the product.

6. The composite peeling layer according to claim 5, characterized in that: The mass ratio of the chromium sulfate, boric acid, ammonium acetate and sodium dodecyl sulfate is 20-100:60-80:10-40:0.01-0.

1.

7. The composite peeling layer according to claim 5, characterized in that: The electroplating temperature is 20-50°C; the current density is 0.5-1 mA / cm 2 , the plating time is 5-30s.

8. Use of the composite peeling layer according to any one of claims 1 to 7 in the preparation of ultra-thin copper foil.

Citation Information

Patent Citations

  • Preparation method for ultrathin copper foil Ni-Cr-B-P stripping layer

    CN107475698A

  • A plating solution for a copper foil release layer and a method for preparing the release layer.

    CN108330517B

  • Preparation method of easy-to-peel ultra-thin carrier-attached copper foil with pure interface

    CN112853408A

  • Method for preparing self-stripping ultrathin copper foil by using discrete chromium crystal nucleus

    CN113388868A

  • Preparation method of ultrathin copper foil based on crystalline-amorphous composite stripping layer

    CN115948773A